Internationalisation through South-North mobility: Experiences and outcomes of research capacity-building programmes for African scholars in Denmark - Hanne Kirstine Adriansen; Lene Møller Madsen (University of Johannesburg, 2021)
Internationalisation of higher education in the global South manifests in different ways through different modalities. Using a multi-disciplinary mobility-lens, this paper discusses outcomes of geographical mobility practiced by African scholars going to universities in the global North as part of research capacity-building programmes. Over the past 30 years, Danida (Danish International Development Assistance) has provided financial assistance - including research visits at Danish universities - to academics in the global South, who would work with problems in their home countries. This type of internationalisation through research capacity building is used in many European countries and is interesting because it facilitates geographical mobility across the North-South socio-economic divide. Based on a survey sent to 499 current and former African scholars as well as 15 qualitative interviews, the aim of this paper is to analyse the reflections from African academics being involved in this type of internationalisation practice. Thereby we give voice to scholars from the global South who are the practitioners of South-North mobility. More specifically, we analyse the role of different locations for becoming an academic and for their knowledge production. Thus, the paper critically examines the impact made by 'internationalisation as mobility' on the personal and professional development of African academics.